Cost containment and managed care: Evidence from German macro data - Andree Ehlert; Dirk Oberschachtsiek; Stefan Prawda (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
The major German health care reforms undertaken since the late 1990s resulted in the adoption of selective contracting mechanisms in a formerly sectorally separated health care system. These reforms marked the launch of managed care in Germany that is expected to yield both a higher quality of care and cost containment. We investigate if managed care had an in uence on the structure of health care expenditure in Germany during the start-up phase of managed care from 2004 to 2008. We focus on pharmaceutical spending by statutory sickness funds (i.e. German law-enforced health insurance). We followed a macroeconomic evaluation approach based on a regional panel data set in contrast to previous research and were thus able to control for a comprehensive set of regional and demographic variables. We discuss alternative model specifications and include a range of sensitivity analyses. Our results suggest that in contrast to public perception the share of managed care contracts has a positive impact on pharmaceutical spending.
Keywords: I11; I18; L14; O52; 330; Managed care; Health care expenditure; Pharmaceutical expenditure; Panel data; German health care reform